Does acupuncture ameliorate motor impairment after stroke? An assessment using the CatWalk gait system. (July 2017) - Cao, Yan; Sun, Ning; Yang, Jing-Wen; Zheng, Yang; Zhu, Wen; Zhang, Zhen-Hua; Wang, Xue-Rui; Shi, Guang-Xia; Liu, Cun-Zhi
Abstract: The effect of acupuncture on gait deficits after stroke is uncertain. This animal study was designed to determine whether acupuncture improves gait impairment following experimentally induced ischemic stroke. Ischemic stroke was induced by permanent middle cerebral artery occlusion (MCAO) in rats. After 7 days' of acupuncture treatment, assessment of gait changes using the CatWalk automated gait analysis system was performed. Comparison of the CatWalk gait parameters among the groups showed that gait function was impaired after ischemic stroke and acupuncture treatment was effective in improving a variety of gait parameters including intensity, stance and swing time, swing speed and stride length at postoperative day 8. This study demonstrates a beneficial effect of acupuncture on gait impairment in rats following ischemic stroke. Further studies aimed to investigate the effects of acupuncture at different stages during stroke using the CatWalk system are required. Highlights: Gait function was impaired after ischemic stroke, especially a persistent reduction in paw intensity. Acupuncture treatment was effective in improving a variety of gait parameters including paw intensity, stance and swing time, swing speed and stride length. The present study is first to assess gait improvement in stroke rats after acupuncture treatment using CatWalk automated gait analysis system.